Dual-Donor-Induced Crystallinity Modulation Enables 19.23% Efficiency Organic Solar Cells - Liang, Anhai; Sun, Yuqing; Chung, Sein; Shin, Jiyeong; Sun, Kangbo; Zhu, Chaofeng; Zhao, Jingjing; Zhao, Zhenmin; Zhong, Yufei; Zhang, Guangye; Cho, Kilwon; Kan, Zhipeng (Nano-Micro Letters, 2024)
Trap-assisted charge recombination is one of the primary limitations of restricting the performance of organic solar cells. However, effectively reducing the presence of traps in the photoactive layer remains challenging. Herein, wide bandgap polymer donor PTzBI-dF is demonstrated as an effective modulator for enhancing the crystallinity of the bulk heterojunction active layers composed of D18 derivatives blended with Y6, leading to dense and ordered molecular packings, and thus, improves photoluminescence quenching properties. As a result, the photovoltaic devices exhibit reduced trap-assisted charge recombination losses, achieving an optimized power conversion efficiency of over 19%. Besides the efficiency enhancement, the devices comprised of PTzBI-dF as a third component simultaneously attain decreased current leakage, improved charge carrier mobilities, and suppressed bimolecular charge recombination, leading to reduced energy losses. The advanced crystalline structures induced by PTzBI-dF and its characteristics, such as well-aligned energy level, and complementary absorption spectra, are ascribed to the promising performance improvements. Our findings suggest that donor phase engineering is a feasible approach to tuning the molecular packings in the active layer, providing guidelines for designing effective morphology modulators for high-performance organic solar cells. Highlights: 1 By modulating the crystalline properties of the active layer with dual donors, the efficiency of organic solar cells reaches 19.23%. 2 The introduction of PTzBI-dF suppresses the accumulation of traps and charge recombination, allowing ternary devices to maintain 82% of their initial power conversion efficiency (PCE) after illumination for 800 h. 3 The dual-donor strategy for modulating the crystallinity of the active layer is applicable to a variety of Y6 derivatives, and the increase in PCE exceeds 1%.